2018
DOI: 10.1016/j.jtcme.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of antimicrobial and antioxidant potential of ethanolic extract and its fractions of bark and leaves of Terminalia arjuna from north-western Himalayas, India

Abstract: The present study was aimed to evaluate the antimicrobial and antioxidant potential of ethanolic extract and its different solvent fractions (chloroform, ethyl acetate, n-butanol and aqueous fraction) of bark and leaves of Terminalia arjuna. The antimicrobial activity was determined by disc diffusion and minimum inhibitory concentration (MIC) methods against six bacterial stains. The antioxidant activity was evaluated by using DPPH, FRAP and Nitric oxide (NO) scavenging assay. The total phenolics and flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…Through indigenous knowledge [ 4 , 6 8 ], plants and plant parts that confer more efficacy have been identified. However, studies indicate that the nature and quantity of phyto-compounds differs among and within plant species and can be organ dependent within an individual [ 2 , 9 ]. Quantitative or qualitative medicinal properties are also affected by post-harvesting processes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through indigenous knowledge [ 4 , 6 8 ], plants and plant parts that confer more efficacy have been identified. However, studies indicate that the nature and quantity of phyto-compounds differs among and within plant species and can be organ dependent within an individual [ 2 , 9 ]. Quantitative or qualitative medicinal properties are also affected by post-harvesting processes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…similar to present study, study on ethanolic extract and its fraction of T. arjuna showed that the fraction enriched with phenolic and flavonoid content showed more antimicrobial and antioxidant activity as compared to crude ethanolic extract. 51 The results suggested that antibacterial and antioxidant activity of plant extracts also depend on the type of solvent also.…”
Section: Discussionmentioning
confidence: 99%
“…Similar extracts had antimicrobial effects on four species that induce acne (P. ovale, P. acnes, P. aeruginosa, and S. aureus)i n broth dilution tests with effects depending on the extract concentration, but no further information was available [49]. Moreover, a leaf extract (0.04 mg/well) was reported as a bactericidal agent against S. aureus and fungistatic against C. albicans [52]. Contrarily, extracts of 130 and 200 mg/mL from aerial parts were unable to prevent the growth of 34 microorganisms from genera Bacillus, Enterobacter, Klebsiella, Listeria, Pseudomonas, Salmonella, Staphylococcus, Aspergillus, and Candida, among others; therefore, it was considered inactive at these concentrations in a disc diffusion assay [66].…”
Section: Human Pathogensmentioning
confidence: 99%